2023
DOI: 10.3390/curroncol30090602
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment for Older Women with Early-Stage (Non-Metastatic) Breast Cancer—An Updated Systematic Review of the Literature

Chantae Reid-Agboola,
Anita Klukowska,
Francesca L. Malcolm
et al.

Abstract: Background: A previous systematic review by our team (2012) undertook comprehensive geriatric assessment (CGA) in breast cancer and concluded there was not sufficient evidence to instate CGA as mandatory practice. SIOG/EUSOMA guidelines published in 2021 advocate the use of CGA in breast cancer patients. The aim is to perform an updated systematic review of the literature. Methods: A systematic review of studies published between 2012 and 2022 that assessed the use of CGA in breast cancer was performed on Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…A recent systematic review of utilization of CGA in older women with early stage non-metastatic breast cancer suggested that results of the CGA can be successfully used to assess QOL and predict treatment outcomes (e.g. survival and mortality rate) [ 66 ]. As such, CGA may assist with identifying varying levels of fitness of patients based on an algorithm of factors to determine the most optimal treatment options that increase chances of survival, minimize treatment adverse effects, and decrease risk for poorer physical HrQOL outcomes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of utilization of CGA in older women with early stage non-metastatic breast cancer suggested that results of the CGA can be successfully used to assess QOL and predict treatment outcomes (e.g. survival and mortality rate) [ 66 ]. As such, CGA may assist with identifying varying levels of fitness of patients based on an algorithm of factors to determine the most optimal treatment options that increase chances of survival, minimize treatment adverse effects, and decrease risk for poorer physical HrQOL outcomes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…survival and mortality rate) [ 66 ]. As such, CGA may assist with identifying varying levels of fitness of patients based on an algorithm of factors to determine the most optimal treatment options that increase chances of survival, minimize treatment adverse effects, and decrease risk for poorer physical HrQOL outcomes [ 66 ]. Although there is no current gold standard for CGA, our results suggest that age, number of comorbidities, BMI, and financial hardship may be important domains to consider.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the heterogeneous nature of the disease and the paucity of evidence specific to older persons, managing breast cancer in this population is challenging [ 5 ]. The under-representation and exclusion of elderly persons from clinical studies led to major gaps in evidence regarding the evaluation and treatment of this population [ 6 , 7 ]. The few studies that focused specifically on breast cancer in elderly women provided some details about the clinicopathological features of the disease in this group and showed that it differs uniquely from the features of the disease in the younger population [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%